Chromosome-Level Genome Assemblies of Two Hypnales (Mosses) Reveal High Intergeneric Synteny. (15th February 2022) - Yu, Jin; Cai, Yuqing; Zhu, Yixin; Zeng, Yuying; Dong, Shanshan; Zhang, Kexin; Wang, Sibo; Li, Linzhou; Goffinet, Bernard; Liu, Huan; Liu, Yang
Abstract: Mosses compose one of the three lineages of bryophytes. Today, about 13, 000 species of mosses are recognized from across the globe, and at least one-third of this diversity composes the Hypnales, a lineage characterized by an early rapid radiation. We sequenced and de novo assembled the genomes of two hypnalean mosses, namely Entodon seductrix and Hypnum curvifolium, based on the 10x genomics and Hi-C data. The genome assemblies of E. seductrix and H. curvifolium comprise 348.4 and 262.0 Mb, respectively, estimated by k -mer analyses to represent 93.3% and 97.2% of their total genome size. Both genomes were assembled at the chromosome level, with scaffold N50 of 30.0 and 20.7 Mb, respectively. The annotated genome of E. seductrix comprises 25, 801 protein-coding genes and that of H. curvifolium 29, 077, estimated to represent 96.8% and 97.2%, respectively, of the total gene spaces based on BUSCO (Benchmarking Universal Single-Copy Ortholog) assessment. For both genomes, most contigs were anchored to the largest 11 pseudomolecules, corresponding to the 11 chromosomes of the two species, and each with a putative sex-related chromosome characterized by low gene density. The chromosomes of E. seductrix and H. curvifolium are highly syntenic, suggests limited architectural shifts occurred following the rapid radiation of the Hypnales. We compared their genomic features to the model moss Physcomitrium patens . The hypnalean moss genomes lack signatures of recent whole-genome duplication. The presented high-quality moss genomes provide new resources for comparative genomics to potentially unveil the genomic evolution of derived moss lineages.